´Síndrome de desgaste profesional (Burnout) en médicos y enfermeras que laboran en los Centros de Salud N°1 N°2 y N°3 de la ciudad de Loja y su relación con la calidad de atención brindada a los usuarios. - Medina Chamba, Jackson Eduardo (2013)
Being a doctor or nurse is not easy , it is a great responsibility , it is to be in charge of human beings in times when life and death are facing , this entails an erosion of emotional resources , which if not handled well bring been a decline in mental health level , which can somatize and see committed the biological state of health , which determines a negative charge for the institution in which they work, and for the National Health System , resulting in a population unsatisfied , not well attended and health problems solved little or nothing . The research work, is descriptive and cross whose objective is to identify the presence of burnout syndrome among physicians and nurses working in health centers N ° 1, N ° 2 and N ° 3 of the city of Loja , and its relation to key variables such as age , gender , marital status , place and length of service , and in turn influence the quality of care provided to users, this test by applying the Maslach Burnout Inventory (MBI) (annex 1) and the questionnaire to evaluate the perceived quality of care in nursing homes SERVQHOS (SERVICES QUALITY HOSPITAL) (annex2). The Common that were applied in April and May 2012, 54 doctors, 26 nurses and 200 external users. Following analysis of the results showed that the frequency of Burnout was 21.25 % (17 ) , of which 12.5 % (10) are doctors and 8.75 % (7) are nurses , mostly women (65%), married ( 65%) , aged 31-40 years ( 47%), with <1 year of work experience (47%) work more than 8 hours per day (53%) and mostly belonging to the Health Center N 3 ( 47%). Finally, 53 % (108) user defined quality of care , and quality Media Keywords: Burnout Syndrome, health professionals, health care quality.